Tata Kelola Keuangan Kongsi Kematian Masjid “X” Kota Padang sebagai Entitas Sosial Bernilai Moneter - Liesma Maywarni Siregar; Winbaktianur (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Death sharing has become a part of community life in many regions in Indonesia, necessitating proper financial management. Good financial governance within these social groups can provide peace of mind and minimize the potential for conflict between members and administrators. This study aims to examine the management of funds in the social group of the Death Company. This research used a qualitative method with data collection techniques through interviews. The results of this study indicate that the existence of Kongsi Death social group is needed in carrying out social activities, for example to visit the member when get sick, compensation for condolences for those who misfortune/death, marriage, or related events such as thanksgiving celebration. The nature of membership of this community is voluntary and each member is required to pay certain fees to help each other if there are any social activities. and also have some assets such as cooking equipment, grave land and ambulances. For this reason, good practice of financial management is needed to manage the funds so that they are right on target and transparent and useful. With good financial governance in the social association, it can provide peace and minimize the potential for conflict between members and administrators in this community.